Man using the SpinPro Ultracentrifugation Expert System (1980)
Designed to run on the IBM Personal Computer XT, the software of the Expert System (according to an article in the April 1986 issue of American Chemical Society) uses "Artificial Intelligence (AI) techniques to design efficient and accurate ultracentrifugation procedures." Users would answer a series of questions about their desired outcomes and parameters, and the software would recommend a procedure. Beckman Instruments began producing centrifuges after their January 1, 1955 acquisition of industry leader, Specialized Instruments Corporation, or Spinco. With Spinco came the famous Model E Ultracentrifuge, which was developed in 1947 and was used for many important scientific discoveries of the 20th century, like the 1957 CalTech experiment that proved James Watson and Francis Crick’s theory on DNA replication. Centrifuges continue to produced under the Beckman name as of 2016.
Keywords: Scientific apparatus and instruments; Centrifuges; Computers--History; Beckman Instruments, Inc.